2021
DOI: 10.1155/2021/2058964
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Helper CD4+ T Cells, Follicular Regulatory CD4+ T Cells, and Inducible Costimulator and Their Roles in Multiple Sclerosis and Experimental Autoimmune Encephalomyelitis

Abstract: Follicular helper CD4+ T (TFH) cells are a specialized subset of effector T cells that play a central role in orchestrating adaptive immunity. TFH cells mainly promote germinal center (GC) formation, provide help to B cells for immunoglobulin affinity maturation and class-switch recombination of B cells, and facilitate production of long-lived plasma cells and memory B cells. TFH cells express the nuclear transcriptional repressor B cell lymphoma 6 (Bcl-6), the chemokine (C-X-C motif) receptor 5 (CXCR5), the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 110 publications
2
18
0
Order By: Relevance
“…In this study, we investigated the involvement of Tfh cells in MS. Several studies have reported dysregulated levels of Tfh and Tfr cells in blood from patients with MS suggesting their importance in disease pathogenesis. 6 , 17 , 27 However, there are discrepancies between studies reporting both elevated and similar frequencies of circulating Tfh cells in patients with RRMS compared with healthy controls. 10 , 14 , 15 , 28 This may at least partially relate to differing definitions of Tfh cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated the involvement of Tfh cells in MS. Several studies have reported dysregulated levels of Tfh and Tfr cells in blood from patients with MS suggesting their importance in disease pathogenesis. 6 , 17 , 27 However, there are discrepancies between studies reporting both elevated and similar frequencies of circulating Tfh cells in patients with RRMS compared with healthy controls. 10 , 14 , 15 , 28 This may at least partially relate to differing definitions of Tfh cells.…”
Section: Discussionmentioning
confidence: 99%
“…Follicular helper T (Tfh) cells are a subset of peripheral lymphoid tissue T cells primarily located in germinal centers where they function to promote B-cell differentiation to antibody-producing plasma cells. 4 - 6 Conversely, follicular regulatory T cells (Tfr) function by suppressing the Tfh-induced B-cell response. 7 Phenotypically, both Tfh and Tfr cells express CD4 and the lymphoid follicle-homing chemokine receptor CXCR5, and their expression of programmed cell death protein 1 (PD-1) is induced by cognate antigen activation.…”
mentioning
confidence: 99%
“…The ACD4C has also been considered a key factor in predicting responses to chemotherapy and survival in patients with DLBCL, FL, and MCL. A low level of blood CD4 + T cells was shown to be correlated with inferior survival in DLBCL and FL, but had a negative prognostic effect in MCL, due to the heterogeneity of MCL (13)(14)(15). A study has reported the prognostic role of ACD4C in ENKTL in the past (16), but this study deserves further exploration due to the small number of cases (only 70 patients).…”
Section: Discussionmentioning
confidence: 87%
“…CD4 + T cells play a crucial role in inducing immune responses against tumors and influencing lymphoma outcomes. Clinical studies have reported that enhanced levels of blood CD4 + T cells are related to a better prognosis for various types of NHL, including diffuse large B-cell lymphoma (DLBCL), follicular lymphoma (FL), and mantle cell lymphoma (MCL) (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Given the central role of Tfh cells in providing costimulatory maturation and proliferation signals to B cells, their decrease in frequency after depletion of B cells highlights the importance of direct cell-cell interactions during the immunopathology of MS. Numerous studies underscore the importance of Tfh cells in MS pathophysiology (36, 37, 70) . CXCL13, a chemokine involved in the migration of B cells and Tfh cells (71, 72) , is found to be elevated in the CSF of MS patients (73) and predictive of a more severe disease course (74) .…”
Section: Discussionmentioning
confidence: 99%